A Learning Model Design Integrating ESP Course and Service Learning Program to Promote Relevance and Meaningfulness - Prabandari, Carla Sih; Aji, Gregorius Punto; Yulia, Made Frida (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2016)
Relevance and meaningfulness of the content courses need to beestablished to make learners realize that the knowledge acquired in the clasroomcan be utilized to give contributions to society. This research is aimed at designinga learning model integrating ESP course and Service Learning Program. ESP is asubject designed to enable students to design ESP programs. The integration ofESP and SLP allows students to exercise their skills in designing an ESP program,which is eventually implemented as one of their SLP programs. The currentresearch is targeted to describe what the learning model design integrating ESPCourse and Service Learning Program looks like.